Proceedings of the 14th International Conference on Predictive Models and Data Analytics in Software Engineering 2018
DOI: 10.1145/3273934.3273939
|View full text |Cite
|
Sign up to set email alerts
|

How Effectively Is Defective Code Actually Tested?

Abstract: Background: Newspaper headlines still regularly report latent software defects. Such defects have often evaded testing for many years. It remains difficult to identify how well a system has been tested. It also remains difficult to assess how successful at finding defects particular tests are. Coverage and mutation testing are frequently used to asses test effectiveness. We look more deeply at the performance of commonly used JUnit testing by assessing how much JUnit testing was done and how effective that tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In particular, the authors report that 61% of the analyzed tests contain multiple assertions, and nearly 78% of the assertTrue and assertFalse assertions lack an error message. Petrić et al 89 analyze the effectiveness of unit tests on 7 Java projects (out of a pool of 5508 candidates). They find that only about 30% of defective methods are covered by unit tests.…”
Section: Related Workmentioning
confidence: 99%
“…In particular, the authors report that 61% of the analyzed tests contain multiple assertions, and nearly 78% of the assertTrue and assertFalse assertions lack an error message. Petrić et al 89 analyze the effectiveness of unit tests on 7 Java projects (out of a pool of 5508 candidates). They find that only about 30% of defective methods are covered by unit tests.…”
Section: Related Workmentioning
confidence: 99%
“…In line with this view, Bowes et al investigated the effectiveness of tests using metrics that capture various facets of testing [10]. Consequently, several studies have empirically demonstrated that some metrics, such as the number of asserts [42] and methods invoked [31] by a test, are highly associated with faults. In this work we analyse mutants to identify how tests can be improved to cover specific types of fault.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors have also been investigated in terms of the ability of tests to uncover faults. Most notably, test suite size [19], number of assertions [42] and number of covered methods per test [31] have all been shown to have an effect on test effectiveness. The relationship between fault type and test effectiveness has not been adequately explored.…”
mentioning
confidence: 99%
“…Although it provides good results, it has the disadvantage of requiring inputs or test cases to properly execute the system. Unfortunately, this is not the case in most legacy systems [32].…”
mentioning
confidence: 99%